Association Between Childhood and Adolescent Sexual Abuse Experiences and High-Risk Sexual Behaviors Among Chinese Youth. Issue 4 (1st December 2018) - Ding, Ruoxi; Wen, Xu; He, Ping; Guo, Chao; Luo, Yanan; Song, Xinming; Zheng, Xiaoying
Abstract: Introduction: Adolescents are at high risk for negative health outcomes associated with high-risk sexual behaviors (HRSBs), and researchers have attempted to identify factors that influence such behavior so that meaningful prevention and intervention programs may be developed. Aim: To investigate the associations between CSA experience and HRSBs in Chinese youth aged 15-24 years old. Methods: Data were from the Survey of Youth Access to Reproductive Health in China, a national sample survey conducted in 2009. The following behaviors were classified as HRSBs: condom non-use during the first sexual experience, having sex with multiple partners, taking part in casual sex, engaging in commercial sex, taking part in anal sex, and condom non-use during the most recent sexual encounter. Differences in HRSBs between the sexes were examined. The χ 2 test and binary logistic regression were used to estimate the association between CSA experience and HRSBs. Main Outcome Measure: The sexual behaviors of condom non-use during the first sexual experience, sexual activity with multiple partners, taking part in casual sex, engaging in commercial sex (defined as paying or receiving money/gifts in exchange for sex), taking part in anal sex, and condom non-using during the most recent sexual intercourse were classified as HRSBs. Results: 4, 974 Sexually active youth were included in this study, 150 respondents (3.0%) reported CSA experience, and 3, 950 (79.4%) sexually active youth had engaged in at least 1 type of HRSBs. The odds of having sex with multiple partners (odds ratio [OR] 4.31, 95% CI 3.07–6.07), casual sex (OR 3.65, 95% CI 2.55–5.24), commercial sex (OR 7.43, 95% CI 5.13–10.77), anal copulation (OR 2.54, 95% CI 1.57–4.12), or any of these HRSBs (OR 5.02, 95% CI 2.33–10.80) were significantly higher among those who had experienced CSA. There was a gender-specific difference in the associations of CSA with different types of HRSBs. Conclusion: Sexual abuse experience in childhood is highly correlated with HRSBs among Chinese youth, and the pattern of this association differs between males and females. Public knowledge and social assistance systems needs to be improved for children and youth in China. Gender-specific counter-measures may be more efficient for interventions.